Should we be imaging lymph nodes at initial diagnosis of early‐stage mycosis fungoides? Results from the PROspective Cutaneous Lymphoma International Prognostic Index (PROCLIPI) international study. (10th September 2020) - Hodak, E.; Sherman, S.; Papadavid, E.; Bagot, M.; Querfeld, C.; Quaglino, P.; Prince, H.M.; Ortiz‐Romero, P.L.; Stadler, R.; Knobler, R.; Guenova, E.; Estrach, T.; et al.
Summary: Background: Early‐stage mycosis fungoides (MF) includes involvement of dermatopathic lymph nodes (LNs) or early lymphomatous LNs. There is a lack of unanimity among current guidelines regarding the indications for initial staging imaging in early‐stage presentation of MF in the absence of enlarged palpable LNs. Objectives: To investigate how often imaging is performed in patients with early‐stage presentation of MF, to assess the yield of LN imaging, and to determine what disease characteristics promoted imaging. Methods: A review of clinicopathologically confirmed newly diagnosed patients with cutaneous patch/plaque (T1/T2) MF from PROspective Cutaneous Lymphoma International Prognostic Index (PROCLIPI) data. Results: PROCLIPI enrolled 375 patients with stage T1/T2 MF: 304 with classical MF and 71 with folliculotropic MF. Imaging was performed in 169 patients (45%): 83 with computed tomography, 18 with positron emission tomography–computed tomography and 68 with ultrasound. Only nine of these (5%) had palpable enlarged (≥ 15 mm) LNs, with an over‐representation of plaques, irrespectively of the 10% body surface area cutoff that distinguishes T1 from T2. Folliculotropic MF was not more frequently imaged than classical MF. Radiologically enlarged LNs (≥ 15 mm) were detected in 30 patients (18%); only seven had clinical lymphadenopathy. On multivariate analysis, plaque presentation was the sole parameter significantly associated with radiologically enlarged LNs. Imaging of only clinically enlarged LNs upstaged 4% of patients (seven of 169) to at least IIA, whereas nonselective imaging upstaged another 14% (24 of 169). LN biopsy, performed in eight of 30 patients, identified N3 (extensive lymphomatous involvement) in two and N1 (dermatopathic changes) in six. Conclusions: Physical examination was a poor determinant of LN enlargement or involvement. Presence of plaques was associated with a significant increase in identification of enlarged or involved LNs in patients with early‐stage presentation of MF, which may be important when deciding who to image. Imaging increases the detection rate of stage IIA MF, and identifies rare cases of extensive lymphomatous nodes, upstaging them to advanced‐stage IVA2. Abstract : What is already known about this topic? The indication for imaging in presentation of early mycosis fungoides (MF) without clinical lymphadenopathy is controversial. The literature on the outcome of imaging in early‐stage presentation of MF is strikingly sparse. What does this study add? Physical examination seems to be a poor determinant of radiological lymphadenopathy. Whereas enlarged LNs were palpated in only 5% of cases, imaging detected 18% with at least stage IIA MF, mostly with plaques, and even rare cases with extensive lymphomatous nodes, stage IVA2. Plain language summary available online